Asuhan Keperawatan pada An.H dengan Gangguan Sistem Hematologi: Thalasemia di Ruang Anggrek I RSUD dr. Soeselo Kabupaten Tegal - Wafa Hilmi Hamidah; Esti Nurjanah; Tati Karyawati (STIKes Ibnu Sina Ajibarang, 2024)
Thalassemia is a congenital blood disorder characterized by an abnormal amount of globin chain synthesis, due to a lak of globin chain synthesis (caused by the bone marrow being unable to form the protein needed to produce Hb), resulting in damage to red blood cells, so that a person suffers from anemia (Kemenkes, 2022). The purpose of this writing is to find out and provide nursing care to An.H with hematological system disorders: thalassemia in the Anggrek ward I RSUD dr. Soeselo Kabupaten Tegal in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was found that An.H’s main complaint was weakness. There were three diagnoses found, namely ineffective peripheral perfusion, fatigue and knowledge deficit. Interventions are prepared based on the theory of SDKI, SIKI and SIKI as well as on the client’s condition and can be implemented.